2018
DOI: 10.1177/1056492618818773
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Retirement as an Enterprising Endeavor

Abstract: This article explores issues of age and enterprise in later life as manifested in tensions between retiree and entrepreneurial identities. We utilize the concept of a discursive event to examine time-bound online data, specifically media texts and reader comments associated with the online news coverage of an insurance company report. This report introduced the label Weary to describe “working entrepreneurial and active retirees.” Our analysis shows how keeping healthy and active are constructed as insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Active involvement in working life has become an imperative even in retirement, and entrepreneurship is encouraged as an option for becoming employed at an older age to prolong careers and prevent early retirement (Ainsworth and Hardy, 2008;Tomlinson and Colgan, 2014;Kautonen et al, 2017). However, in contrast to startup/growth and expert entrepreneurship senior entrepreneurship is labeled as "modest" and, thus, undermined in terms of economic growth (see also Whiting and Pritchard, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active involvement in working life has become an imperative even in retirement, and entrepreneurship is encouraged as an option for becoming employed at an older age to prolong careers and prevent early retirement (Ainsworth and Hardy, 2008;Tomlinson and Colgan, 2014;Kautonen et al, 2017). However, in contrast to startup/growth and expert entrepreneurship senior entrepreneurship is labeled as "modest" and, thus, undermined in terms of economic growth (see also Whiting and Pritchard, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, prior studies worldwide, as we indicate below, have shown that entrepreneurship is a rather restrictive category to which only a few special individuals have access. An ideal entrepreneur is associated with youth, middle-classness and masculinity (Komulainen, 2006;Ainsworth and Hardy, 2008;Komulainen et al, 2009;Hytti and Heinonen, 2013;Gill, 2014;Whiting and Pritchard, 2020). Villasana et al (2016) showed that Latin American male students reported feeling more creative and better at managing problems and risks than women, and thus indicating greater potential as entrepreneurs.…”
Section: The Construction Of Ideal Entrepreneursmentioning
confidence: 99%
“…It has been suggested that the virtual nature of exchanges can reduce the stigma experienced by marginalised groups, reduce risk and help overcome high barriers to entry, enabling wider economic participation (Jome et al, 2006). This message is targeted specifically at marginalised people who experience structural barriers to employment and career progression, particularly mothers, retirees, disabled people, young people, and people of colour (Accenture, 2014;Genachowski, 2011;Whiting and Pritchard, 2018;Women Entrepreneurs UK, 2010). By this rhetoric, people from these groups and their intersections are encouraged to embrace entrepreneurship, empower themselves, and in turn, advance the economy.…”
Section: Claim 2: Digital Enterprise Empowers Marginalised People and Economiesmentioning
confidence: 99%
“…People may have freedom and autonomy, financial independence and more time for family, leisure, hobbies and travel. In contrast, Whiting and Pritchard (2018), examined 'the weary', a label coined to refer to working entrepreneurial and active retirees, highlighting the destabilisation of retirement and its discursive re-conceptualisation as a period of entrepreneurial endeavour. Driver (2017) highlighted the critical importance of being active and purposeful and remaining an attractive labour commodity.…”
Section: Reasons To Retire/ Continue To Workmentioning
confidence: 99%